Book Review: Inclusive Education: Stories of Success and Hope in a Canadian Context - Gooderham, Suzanne (Journal of the Canadian Association for Curriculum Studies, 2017)
In their book, Inclusive Education: Stories of Success and Hope in a Canadian Context (2018), Stegemann and AuCoin have created an exceptional collection of case studies that illustrate what is possible when a firm belief in inclusion in its deepest sense is combined with a spirit of collaboration and co-operation. The nine case studies include students with unique and complex learning needs at different stages of their educational career. A wide range of exceptionalities and levels of ability are presented in different settings across Canada. While this diversity makes the book interesting and informative, it is the inclusion of multiple perspectives and the actual voices of the individuals involved that results in a compelling and important resource for both pre-service and in-service educators.